Integrating Islamic Principles with Modern Legal Frameworks: Addressing Children’s Origin in Religious Courts - Sistyawan, Dwanda Julisa; Harmono, Harmono; Judijanto, Loso; Supaat, Dina Imam; Pakarti, Muhammad Husni Abdulah (Contemporary Issues on Interfaith Law and Society, 2025)
This study investigates the legal complexities in determining the status of children born out of wedlock within the framework of Islamic family law, focusing on cases adjudicated by the Temanggung Religious Court. The research is driven by the increasing number of disputes related to birth records, the evidentiary role of DNA testing, and the legal implications for children's civil status and inheritance rights. Employing a normative legal research method, this study analyzes statutory regulations, authoritative legal literature, and selected court decisions to evaluate how legal norms are applied in actual case resolutions. The study aims to explore several critical issues: the implications of different birth records, the role of DNA testing in establishing paternity, and the legal recognition of children born out of wedlock in Islamic family law. Findings indicate that DNA testing has emerged as a pivotal tool in confirming biological paternity, thereby providing legal certainty and safeguarding children's inheritance rights. However, inconsistencies in birth record documentation often result in ambiguity and pose challenges in determining legal parentage. The jurisprudence of the Temanggung Religious Court demonstrates varied approaches, reflecting both the rigidity and adaptability of current legal interpretations in reconciling religious doctrine with scientific evidence. The study concludes that despite the availability of scientific methods, the absence of uniform legal standards contributes to inconsistencies in the protection of children's rights. Legal reform is therefore necessary to harmonize Islamic legal principles with modern evidentiary practices. Strengthening procedural clarity and integrating scientific proof within religious adjudication frameworks will promote a more equitable and rights-based approach in family law, particularly in matters of parentage and inheritance.